2007
DOI: 10.1007/s00701-007-1230-1
|View full text |Cite
|
Sign up to set email alerts
|

Deep brain stimulation in the subthalamic area is more effective than nucleus ventralis intermedius stimulation for bilateral intention tremor

Abstract: SummaryBackground. The ventro-lateral thalamus is the stereotactic target of choice for severe intention tremor. Nevertheless, the optimal target area has remained controversial, and targeting of the subthalamic area has been suggested to be superior.Patients and methods. Eleven patients with disabling intention tremor of different etiology (essential tremor (n ¼ 8), multiple sclerosis (n ¼ 2) and one with, spinocerebellar ataxia) were implanted bilaterally with DBS electrodes targeted to the ventro-lateral th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
95
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(104 citation statements)
references
References 60 publications
8
95
0
1
Order By: Relevance
“…The posterior subthalamic area (PSA) is situated immediately inferior to the VIM and posteromedial to the subthalamic nucleus (STN). Cerebellothalamic axons are particularly dense within the PSA before dispersing into the VIM, and promising results have been reported regarding DBS in this area [5,6,7,8,9]. One plausible explanation for the effectiveness of PSA DBS is that stimulation of axons instead of nuclei actually affects more neurons and therefore also alters tremor oscillations more efficiently [3,4,10].…”
Section: Introductionmentioning
confidence: 99%
“…The posterior subthalamic area (PSA) is situated immediately inferior to the VIM and posteromedial to the subthalamic nucleus (STN). Cerebellothalamic axons are particularly dense within the PSA before dispersing into the VIM, and promising results have been reported regarding DBS in this area [5,6,7,8,9]. One plausible explanation for the effectiveness of PSA DBS is that stimulation of axons instead of nuclei actually affects more neurons and therefore also alters tremor oscillations more efficiently [3,4,10].…”
Section: Introductionmentioning
confidence: 99%
“…The overall activity was reduced in the SA, usually beginning within 1 mm from the intercommissural level. 13 After confirmation of neural activity, we performed macrostimulation by using the outer cannula of the microelectrode, with a contact point length of 1 mm, from 2-4 mm below the target to 2-4 mm above the target at 1-to 2-mm intervals to confirm the effects of stimulation on the tremor. We were concerned about brain shift due to leakage of CSF during surgery.…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…Only one report comparing the effects of thalamic and SA stimulation on tremor has been published, and this study indicated that SA stimulation is more effective than VIM nucleus stimulation at treating intentional tremor. 13 Since the underlying pathology involves a structural lesion, a variable combination of neural elements is damaged, giving rise to a rich variety of tremor phenomenology in HT. 8 Further studies are thus needed to clarify the optimal stimulation sites for exerting effects on each tremor component of HT.…”
Section: Optimal Stimulation Site For the Tremor Components Of Htmentioning
confidence: 99%
“…Then, as recent evidence suggests, the subthalamic nucleus could be considered a better target for neurosurgical treatment of ET than the VIM. 7,8 Copyright © 2012 by AAN Enterprises, Inc.…”
mentioning
confidence: 99%